Identification of mcr-1-positive multidrug-resistant Escherichia coli isolates from clinical samples in Shanghai, China. (June 2022) - Xie, Jing; Liang, Beibei; Xu, Xuebin; Yang, Lang; Li, Huan; Li, Peng; Qiu, Shaofu; Song, Hongbin
Highlights: Of the faecal samples obtained from clinical settings in Shanghai, 3.9% were mcr-1 -positive Escherichia coli strains. All mcr-1 was detected in four types of E. coli, including atypical enteropathogenic E. coli (aEPEC), enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), and enteroaggregative E. coli (EAEC). Half of the strains carrying quinolone resistance- or β-lactam resistance-related genes were multidrug-resistant. IncX4 was the predominant type in mcr-1 -positive E. coli . ABSTRACT: Objectives: Since the gene encoding mobilised colistin resistance ( mcr-1 ) was first reported in China in 2015, it has been reported in various Enterobacteriaceae worldwide. Escherichia coli, one of the main pathogens causing diarrhoea, is the most prevalent, clinically identified species carrying mcr-1 . This study aimed to investigate the epidemiologic and genomic characteristics of mcr-1 in Escherichia coli from patients in Shanghai. Methods: Faecal samples were collected from hospitals in Shanghai between 2012 and 2015. Polymerase chain reaction was performed to detect mcr-1, and molecular characteristics of the mcr-1 -positive E. coli was determined by antimicrobial susceptibility testing and whole-genome sequencing. Results: We detected 40 (3.9%) mcr-1 -positive E. coli strains from faecal samples in clinical settings between 2012 and 2015 in Shanghai. Mcr-1 was detected in 4 types of E. coli, including atypical enteropathogenic E. coli (aEPEC), enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), and enteroaggregative E. coli (EAEC). Most strains harbouring mcr-1 were isolated from children aged <7 years. Whole-genome sequencing revealed that nearly half of the strains that carried quinolone resistance- or β-lactam resistance-related genes were multidrug-resistant. IncX4 was the predominant type in mcr-1 -positive E. coli in Shanghai, but the other types of mcr-1 -harbouring plasmids are highly diverse in genetic context. Conclusion: These data suggest that mcr-1 is prevalent in E. coli strains, especially those identified in diarrhoeal patients in Shanghai, and strengthening the surveillance of mcr-1 transmission, especially in children, is essential.